Extended cave drip water time series captures the 2015 – 2016 El Niño in Northern Borneo - Ellis, Shelby A.; Cobb, Kim M.; Moerman, Jessica W.; Partin, Judson W.; Bennett, A. Landry; Malang, Jenny; Gerstner, Hein; Tuen, Andrew A. (American Geophysical Union, 2020)
Time series of cave drip water oxygen isotopes (δ18O) provide site-specific assessments of the contributions of climate and karst processes to stalagmite δ18O records employed for hydroclimate reconstructions. We present ~12 year-long time series of biweekly cave drip water δ18O variations from three sites as well as a daily-resolved local rainfall δ18O record from Gunung Mulu National Park in Northern Borneo. Drip water 18O variations closely match rainfall 18O variations averaged over the preceding 3-18 months. We observe coherent interannual drip water δ18O variability of ~3 to 5‰ related to the El Niño-Southern Oscillation (ENSO), with sustained positive rainfall and drip water δ18O anomalies observed during the 2015/2016 El Niño. Evidence of non-linear behavior at one of three drip water monitoring sites implies a time-varying contribution from a longer-term reservoir. Our results suggest that well-replicated, high-resolution stalagmite 18O reconstructions from Mulu could characterize past ENSO-related variability in regional hydroclimate.